Cognitive networking of large scale wireless systems. (22nd June 2009) - Song, Liang; Hatzinakos, Dimitrios
We propose the concept of cognitive networking for large-scale wireless systems, which opportunistically utilises network resources including both spectrum bandwidth and radio availability. Both types of resources cannot be predetermined in large-scale wireless systems, due to various reasons such as interferences and dynamic traffic load. The proposed technology not only establishes dynamic wireless networks, but also provides for reliable network quality of services (QoS). The supporting network architecture, embedded wireless interconnect (EWI), is proposed to implement the cognitive networking concept and supply an effective application-programming interface for large-scale data management systems. Two example applications are presented, including wireless mesh networks for broadband wireless internet access and wireless sensor networks for target tracking. Major advantages of the technology are further discussed. We suggest that the performance of the proposed system would improve with larger network scale and the implementation complexity could be independent of the network scale.